3(12-5y)=9(2-y)+6(3-y)

Simple and best practice solution for 3(12-5y)=9(2-y)+6(3-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(12-5y)=9(2-y)+6(3-y) equation:



3(12-5y)=9(2-y)+6(3-y)
We move all terms to the left:
3(12-5y)-(9(2-y)+6(3-y))=0
We add all the numbers together, and all the variables
3(-5y+12)-(9(-1y+2)+6(-1y+3))=0
We multiply parentheses
-15y-(9(-1y+2)+6(-1y+3))+36=0
We calculate terms in parentheses: -(9(-1y+2)+6(-1y+3)), so:
9(-1y+2)+6(-1y+3)
We multiply parentheses
-9y-6y+18+18
We add all the numbers together, and all the variables
-15y+36
Back to the equation:
-(-15y+36)
We get rid of parentheses
-15y+15y-36+36=0
We add all the numbers together, and all the variables
=0
y=0/1
y=0

See similar equations:

| 188=13(s-55)+45 | | y=5(850)-1000 | | 6(7.5-1y)-y=-4 | | 5y-1=4y-5 | | y=-(850)+2000 | | y=-5(850)+3500 | | 9/4x-6=28.5 | | y=(850)-1000 | | y=5(850)+1000 | | y=0.42×64T | | 4(0)-5x=10 | | 7^3x=8^2x | | x+4/2-6=2x-8/3 | | -3y+5(1y-1)=7-6(7-y) | | 4x-5(0)=10 | | -4(y-4y)+3=-3(2y-y)+1+14y | | .2x=x-212 | | x^2-121x+120=0 | | 7+3x=9x-11 | | 8(2n+2)=8(8n+4)+9 | | 2x+10+4-36+4x-34=180 | | x/2+x/3=x/6+4 | | 6x/11=5x/8-7 | | 5(x-3)=17-3x | | 10x+14−4x=−8x−5+x | | H(t)=1250(0.865)^t | | -a+7=26 | | 4y/3+y/15=21/5 | | 12x+31-(4-8)=15 | | x-26+x+28+x=180 | | 5/6y-2/3y=3/8 | | 7+4/5x=9/10x |

Equations solver categories